RANCANG BANGUN SISTEM RECORDING BOBOT BADAN SAPI BERBASIS INTERNET OF THINGS - Citra Trilaksana; Adharul Muttaqin; Onny Setyawati (Jurnal Mahasiswa TEUB, 2022)
In 2021, the trend for beef production in indonesia is likely to decline, not in line with the increase in the cattle population. According to the Directorate General of Livestock and Animal Health, Indonesia's beef production was 437,783.23 tons, a decrease of 3.44 percent compared to 2020 of 453,418 tons (Qodriyatun, 2022). The reduced supply of beef in Indonesia is due to the weak synchronization between reproduction management and butchering. The reason is that 78% of national beef production comes from smallholder farms (Zakiah, et al, 2017). In the recording studio, the people are still getting less attention. Recording is all types of recording activities such as assistance activities, genealogical records, production and reproduction records, maintenance management records and livestock health records in certain populations. The Internet of Things (IoT) can be applied to various aspects, especially as a system for recording, storing, sorting and processing data. This application can be used in the system for recording body weight of cattle. For this reason, a system for recording body weight based on the internet of things was designed. The internet of things based body weight recording system uses 2 Load Cell sensors to weigh the body weight of the cow and an RFID sensor to read the identity of the cow, besides that the sensor system has a website as a user interface. It is hoped that this application can increase the efficiency of the process of recording body weight of cattle and produce an intelligent tool system. Keywords: IoT, Recording, Load Cell, RFID